Implementasi Sistem Informasi Manajemen Keimigrasian (SIMKIM) Terintegrasi Sebagai Jembatan Keterkaitan Praktik Hukum Bisnis dan Hukum Keimigrasian Secara Seimbang - Simamora, Agato P. P. (Universitas Ekasakti, 2023)
This research aims to provide a comprehensive picture and description of the use of integrated Immigration Management Information System (SIMKIM) as a bridge connecting the application of business law and the actualization of immigration law, so as to obtain a real picture of the benefits of using integrated SIMKIM as a bridging tool. Research method with a normative juridical approach, primary data obtained through field observations and interviews at the Directorate General of Immigration. The result is an increase in international and transnational crimes, such as: Illegal immigrants, human smuggling, human trafficking, terrorism, narcotics, and money laundering; Immigration law enforcement has not been effective so that the punishment policy needs to include a minimum penalty for human smuggling crimes; Expanding the subject of immigration crimes, so that it includes not only individuals but also corporations and guarantors of the entry of foreigners into Indonesian territory who violate immigration provisions; and the application of more severe criminal sanctions against foreigners who violate regulations in the field of immigration because so far it has not caused a deterrent effect. It is concluded that SIMKIM is a unity of various data and information management processes, applications, and information and communication technology-based devices built to unify and connect information systems in all immigration function implementers in an integrated manner. In this system, there are foreigners both as workers and business actors who are subject to business law provisions such as Law Number 11 of 2020 concerning Job Creation and immigration law provisions. The regulation and control of foreign workers working in Indonesia is based on Article 27 paragraph (2) of the 1945 Constitution of the Republic of Indonesia.